Up The Down Staircase: COVID-19 Paves way for Modern Authoritarianism - Mohan, Nikita; Hooda, Sanjana (Kathmandu School of Law Review, 2020)
The global pandemic has shaken the foundational notions that characterize modern society. A host of rights that dignify our life have had to be sacrificed, with the new ‘normal’ arguably resembling a life reduced to mere existence. Moving into the post-COVID world, we must critically appraise our condition. This essay attempts perspectives on some of the political implications of COVID-19. Through a consideration of ancient philosophies of the likes of Plato and Aristotle, the justification for the institution of the State and why humankind resorts to it, especially in times of crises, has been established. Further consideration of the State’s responses to past global crises, of the Spanish Flu and the Influenza Pandemic, help one understand how such an institution often rules out political concerns and motivations, as opposed to serving the ‘common good’. This is followed by a discussion of the advent of contemporary authoritarianism in the post-COVID world and on the ideology of populism. The concluding part of this essay deliberates on the political landscape of the post-COVID world. While the authors are in no position to conclusively lay down what the post-COVID world will bring forth, they encourage viewing the pandemic as an opportunity to re-evaluate our political choices and rediscovering the power of mutual aid and solidarity as we refuse to return to ‘normal’, rather than treating COVID-19 as an irreversible setback for political rights and emancipation. Humankind must thus climb up the down staircase in approaching the post-COVID world.